'"Fuisse in Forma Hominis" belongs to Christ Alone': John Calvin's trinitarian hermeneutics in his Lectures on Ezekiel. Issue 4 (15th October 2015) - Slotemaker, John T.
Abstract: The present article examines John Calvin's trinitarian and christological interpretation of Old Testament theophanies in his Praelectiones on Ezekiel 1. The first section of the article treats Calvin's exegetical principles. It is noted that Calvin defends a strict set of rules for how to interpret Old Testament theophanies: in short, Calvin argues that if a passage presents the divine nature in the form of a human person, that given theophany must be interpreted as a representation of the second person of the Trinity, the Son of God (i.e. Jesus Christ). In defending this position, Calvin examines in great detail various rules for how to interpret Old Testament passages which indicate a plurality within the divine nature (i.e. the Trinity). He defends his exegetical approach to these texts with numerous passages from the New Testament. This examination of Calvin's exegesis is contextualised in two ways. First, it is noted that Calvin's exegesis of these passages is uncharacteristically more 'strict' in its trinitarian and christological reading than one finds in earlier thinkers such as Augustine and Jerome. For example, Augustine argued that Old Testament theophanies which present God in the form of a human being could be understood as the Father, the Son or the Holy Spirit. Augustine, in short, does not think one can definitively determine which member of the Trinity is 'present' in a theophany. Second, it is noted that this surprising development in Calvin's final work is the result of the rising threat of anti-trinitarianism in Transylvania. Thus, the article argues that the rise of Polish anti-trinitarianism not only contributed to Calvin's renewed interest in trinitarian and christological interpretations of the Old Testament, but it also pushed him to develop a more strict set of exegetical rules which govern how such passages are interpreted. Therefore, the article presents a reading of Calvin which strongly suggests that any complete analysis of Calvin's alleged 'Judaising' must develop a historically nuanced methodology. While it is often argued that Calvin hesitates from interpreting Old Testament passages in a strictly trinitarian or christological way, it must be acknowledged that towards the end of his career he radically began to alter his exegetical rules/method given the renewed threat of the anti-trinitarians.